PHARMACOGNOSTIC EVALUATION OF RHIZOME OF CURCUMA PSEUDOMONTANA J. GRAHAM - GURUSIDDESH B. HIREMATH,; BASAPPA B. KALIWAL, (International Journal of Pharma and Bio Sciences, 2014)
The present work carried out to establish the necessary pharmacognostic standards, according to the WHO guidelines for evaluating the plant material of Curcuma pseudomontana J. Graham rhizome. Pharmacognostic parameters such as macroscopic, microscopic, physicochemical constituents, fluorescence analysis, nutritive value, behavior analysis of rhizome powder and TLC studies were performed. Macroscopic and microscopic evaluation of the rhizome show aromatic, fleshy white inside, starch grains, oleoresin cells, and prismatic calcium oxalate crystals. Physicochemical analysis of the rhizome powder showed 8% total ash, 3% acid insoluble ash, 8 % water insoluble ash, 13% sulphated ash, 11.5% water-soluble extractive, 13.5% alcohol soluble extractive and 6.45% loss on drying. Analysis of nutritive value of rhizome showed, rich source of protein, carbohydrate, dietary fibre and minerals. Behavior analysis of rhizome powder showed presence of steroid, tannins, starch, alkaloid, flavonoid and protein. This is the first report on the pharmacognostic studies of Curcuma pseudomontana J. Graham rhizome. The results of pharmacognostic analysis were helpful in developing standards for quality, purity, and sample identification.